The Fortuitous Case: Cultural and Religious Fundamentals of a Juridical Category and a Cosmovision - De Nardi, Loris (2020)
This article proposes a reflection on the cultural and religious fundamentals of the fortuitous case: The legal category called to discipline, from the Roman Law, the consequences (patrimonial, contractual and criminal) of the facts unrelated to the negligence, fault or deceit of the agent, as they are, for example, all events related to threats of natural origin (earthquakes, floods, etc.). In the proposed text it will be shown that the fortuitous case was shaped by the divine and supernatural beliefs of the ancient Greeks and Romans; that this trait, codified during Roman pagan times by the Roman jurist Gayo (II century A.D.), was conserved during the first Christian period, as shown by the Corpus Iuris Civilis of Justinian (VI century A.D.), because the pagan cosmovision related to disasters was received by the Holy Scriptures; and thatfor its conformity with the biblical dictation (and consistent cosmology), this legal category, called to discipline the consequences of disasters related to threats of natural origin, was adopted by the medieval society in general, and by Hispanics in particular, as some norms of the Espéculo and the Siete Partidas.demonstrate.